Effect of polymers and excipients on the release kinetics, bioadhesion, and floatability of metronidazole tablet - Arora, Saahil; RD, Budhiraja (Asian Journal of Pharmaceutics (AJP), 2014)
Stomach-specific floating tablet of metronidazole based on the buoyancy and bioadhesion concept was prepared with a purpose to retain the drug in stomach for longer duration and helps in releasing the drug in the antrum region of gastric mucosa, a safe heaven for Helicobacter pylori.This research work systematically studied the effects of various polymeric blends of bioadhesive polymers namely chitosan and carbopol 971P with low density polymer- methocel K100LV on the desired in vitro drug release profile in the stomach, buoyancy, swelling index, and mucoadhesion of tablet formulation. Chitosan and carbopol 971P concentration significantly influence the in vitro drug release and bioadhesion strength. An increase in buoyancy was observed with increase in Methocel K100LV concentration in the polymeric blend. The increase in buoyancy and drug release was obtained in the presence of microcrystalline cellulose, sodium bicarbonate, and sodium citrate.The optimum formulation provides desired high drug concentration (~35%) during 1 hour and sustained release up to 12 hours, following the Higuchi model. The mechanism of release of metronidazole from the floating bioadhesive tablets was anomalous diffusion transport. The studies indicated successful formulation of gastroretentive compressed tablet with excellent controlled release, mucoadhesion, and hydrodynamic balance.